Effects of S-3307 and PP333 on callus induction and plantlet regeneration of tall fescue tall fescue (Festuca arundinacea Schreb) - QIAN Hai-feng; XUE Qing-zhong (浙江大学学报. 农业与生命科学版)
Effects of synthetic plant growth regulators S-3307 and P333 on tissue culture of tall fescue (Festuca arundinacea Schreb.) were highly correlated with genotypes. Both the concentrations of S-3307 used in the experiment (0.01 mg/L and 0.1 mg/L) led to an increase in the callus induction rate in the cultivars (Gooden and Triple A), but a decrease in other two cultivars (Dixie Green and Houndog 5). P333 promoted callus induction of three cultivars other than Dixie Green. S-3307 and P333 stimulated the callus differentiation of all cultivars tested except Gooden, giving the best differentiation results at the concentration of 0.01 mg/L and 0.1 mg/L respectively. The toxic effects of four tested cultivars on callus induction and differentiation were observed at the higher concentration (>1 mg/L) of both growth regulators.